Faktor pada perilaku Ibu dalam pemberian MPASI anak 6–24 bulan di Puskesmas Perumnas, Kendari - Rosnah .; Kristiani .; Endang Pamungkasiwi Pamungkasiwi (Alma Ata University Press, 2013)
ABSTRACTBackground: The problem of growth among underﬁ ves in Indonesia is related to the number of infants that are givencomplementary feeding since the age of one month. It inﬂ uenced the prevalence of undernourishment 3.25% andmalnutritionat District of Kadia become higher. Those nutrition problem can be affected by inability to provide foods asneeded by members of the family, knowledge and behavior of the family in food selection, cook and distribute the foodin the family. Another problem is lack of mothers' attention to monitor the child growth and developmentObjective: To study the factors associated with mothers' behavior in the supply of complementary breastfeeding toinfants of 6–24 months at Perumnas Health Center Subdistrict of Kadia Kendari Municipality.Method: This analytical study used a cross sectional design and quantitative and qualitative method. Subject were mothers'of underﬁ ves who fulﬁ lled inclusion criteria at the working area of Perumnas Health Center District of Kadia KendariMunicipality. Samples were taken using simple random sampling technique. Research instruments were questionnaireand indepth interview guide. Data analysis used chi square and double logistic regression test. Qualitative data wereanalyzed manually and presented in narration.Result: Predisposition factors signiﬁ cantly associated with mothers' behavior in the supply of complementary breastfeedingwere mothers' education (p=0.025; OR=3.27), family income (p=0.007; OR=4.65), knowledge of mothers (p=0.05;OR=2.75), and mothers' attitude (p=0.027; OR=2.92). Another supporting factor, i.e. participation of mothers in theintegrated service post (posyandu) was signiﬁ cantly associated with behavior in the supply of complementary breastfeeding(p=0.008; OR=3.65). Encouraging factors associated with the behavior of mother in the supply of complementarybreastfeeding were support of the health staff (p=0.005; OR=4.21) and the family (p=0.041; OR=4.22).Conclusion: The result of multivariate analysis showed that the factor most dominantly associated with the behavior inthe supply of complementary breastfeeding was education of mothers (p=0.012; OR=5,40).KEYWORDS: behavior, complementary breastfeeding, infants of 6 – 24 monthsABSTRAKLatar Belakang: Masalah gangguan pertumbuhan balita di Indonesia berkaitan dengan banyaknya bayi yang sudahdiberi makanan pendamping ASI (MPASI) sejak usia kurang dari atau 1 bulan. Hal ini mengakibatkan prevalensi gizikurang dan buruk di Kecamatan Kadia cukup tinggi. Masalah gizi ini dipengaruhi oleh tingkat kemampuan menyediakanpangan sesuai dengan kebutuhan anggota keluarga, pengetahuan dan perilaku keluarga dalam memilih, mengolah,dan membagi makanan di tingkat rumah tangga. Permasalahan lain kurangnya perhatian ibu untuk memantau tumbuhkembang balitanya.Tujuan: Mengetahui faktor-faktor yang berhubungan dengan perilaku ibu dalam pemberian MPASI pada anak usia6-24 bulan di Puskesmas Perumnas Kecamatan Kadia, Kota Kendari.Metode: Jenis penelitian ini adalah analitik dengan rancangan cross sectional, menggunakan metode kuantitatif dan kualitatif. Subjek adalah ibu balita yang memenuhi kriteria inklusi di wilayah kerja Puskesmas Perumnas KecamatanKadia, Kota Kendari. Jumlah sampel sebanyak 97 subjek. Pengambilan sampel secara simple random sampling. Datadikumpulkan dengan panduan wawancara mendalam dan dianalisis dengan Chi-Square dan uji regresi logistik berganda.Data kualitatif dianalisis secara manual dan disajikan dalam bentuk narasi.Hasil: Dari faktor-faktor predisposisi, yang mempunyai hubungan bermakna dengan perilaku ibu dalam pemberian MPASIadalah pendidikan ibu (p=0,025; RP = 3,27), pendapatan per kapita keluarga (p=0,007; RP = 4,65), pengetahuan ibu(p= 0,05; RP= 2,75), dan sikap ibu (p = 0,027; RP=2,92) dengan perilaku pemberian MPASI. Dari faktor pendukung,partisipasi ibu ke posyandu mempunyai hubungan bermakna dengan perilaku pemberian MPASI (p=0,008; RP=3,65),sedangkan dari faktor pendorong yang berhubungan dengan perilaku ibu dalam pemberian MPASI adalah dukunganpetugas kesehatan (p=0,005; RP=4,21) dan dukungan keluarga (p=0,041; RP=4,22). Kesimpulan: Dari hasil analisis multivariat diperoleh hasil bahwa faktor paling dominan yang berhubungan denganperilaku pemberian MPASI adalah pendidikan ibu (p=0,015; RP= 5,40).KATA KUNCI: perilaku, pemberian MPASI, anak usia 6-24 bulan.